Analysis of the Prevalence of Fractures Caused by Bicycle Accidents - Zahir Khan, Asghar Ali, Aimon Zia, Saif Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to examine the epidemiological features of fractures that are received in bike accidents. Study design: Retrospective study Place and duration of study: Department of Orthopedic, Mardan Medical Complex, Mardan for the period of one year from January 2021 to January 2022. Methods: There were 210 patients of bike accidents were analysed through severity scoring system. Various bike types, fractures sustained, rate of mortality, helmet usage was analyzed. Detailed demographics of enrolled cases included age, sex, BMI and localities were recorded after taking informed written consent. Outcomes were assessed in terms of fractures sustained during accidents. We used SPSS-21.0 to analyze our data. Results: There were 54.8% males and 45.2% females. The mean age of the patients was 31.8±6.17 years. We found that 192 (91.4%) patients wear no helmet. The presentation of the injuries showed that majority of the cases 100 (47.6%) had lower limb injuries. The majority of patients with multiple injuries also suffered from upper limb, facial, spinal and chest trauma. Overall mortality rate was 22 (10.5%). Conclusion: We concluded in this study that wearing helmets can reduce the severe life threatening injuries caused by bike accidents. Keywords: bike accidents, fractures. Mortality, multiple injuries